The Indonesian Government’s Regulation on the Management of COVID-19 Hazardous Medical Waste from Health Service Facilities and Self-Isolation Activities - Subadi, Subadi (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: The SARS-CoV-2 virus that causes Covid-19 entered Indonesia in January 2020, though the government firstly announced its entrance on March 2nd, 2020. This pandemic has affected this country for more than two years, and it has caused many casualties and material losses. The Indonesia government still undergoes efforts to prevent the spread of this disease. One of its media of infection is Covid-19 medical waste. It is estimated that Indonesia produces 138 tons of Covid-19 medical waste daily, with limited management capabilities. Objective: This research aims to describe the Indonesian government’s policies or regulations on the acceleration in handling the Covid-19 pandemic, by cutting the chain of infection through the management of hazardous and toxic waste, namely the medical waste from health service facilities and self-isolation activities of Covid-19 sufferers. Method: This research uses the doctrinal approach. Results and discussion: It is shown that the Indonesian government's regulations are well-prepared. But due to the quick spread of the virus, the government needed to issue different regulations several times in order to adapt to the situation in the field. After some time, the vaccination program has reached the target and the quantity of the spread has decreased. Thus, the government issued new policies on the status of the Covid-19 medical waste from the category of hazardous and toxic waste into common domestic waste.